2009
DOI: 10.1038/ki.2008.482
|View full text |Cite
|
Sign up to set email alerts
|

Increased E-cadherin expression in the ligated kidney following unilateral ureteric obstruction

Abstract: E-cadherin expression in the kidney is used as a surrogate marker of epithelial mesenchymal transition for the testing of various antifibrotic strategies. Here we reexamined E-cadherin expression in the kidneys of rats with unilateral ureteric obstruction, which was previously reported to decrease in parallel with the development of tubulointerstitial disease in this widely used experimental model of renal fibrosis and epithelial mesenchymal transition. E-cadherin mRNA expression was consistently increased bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 38 publications
4
15
1
Order By: Relevance
“…In particular, our results showing the absence of EMT in shear-activated PTECs are in accord with prior observations showing that moderate shear stress actually increases renal epithelial intercellular adhesion via the formation of tight and adherens junctions (6). Similarly, our data are consistent with observed increases in cellular E-cadherin resistant to TGF␤1 intervention in a study utilizing unilateral ureteral obstruction, a widely accepted animal model of kidney disease (38). Furthermore, our data suggest that progression of fibrosis and the initiation of the EMT machinery may be mutually exclusive events.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, our results showing the absence of EMT in shear-activated PTECs are in accord with prior observations showing that moderate shear stress actually increases renal epithelial intercellular adhesion via the formation of tight and adherens junctions (6). Similarly, our data are consistent with observed increases in cellular E-cadherin resistant to TGF␤1 intervention in a study utilizing unilateral ureteral obstruction, a widely accepted animal model of kidney disease (38). Furthermore, our data suggest that progression of fibrosis and the initiation of the EMT machinery may be mutually exclusive events.…”
Section: Discussionsupporting
confidence: 92%
“…24 -26 In the UUO animals, miR-200b was significantly down-regulated; this could be an indicator that EMT is occurring in this model and contributing to the myofibroblast cell number. However, E-cadherin expression was up-regulated in this model at this time point (see Supplemental Figure S6 at http://ajp.amjpathol.org), which has been reported before 45 and is in contrast to what was observed in the in vitro model in which E-cadherin was down-regulated. Target analysis of miR-200b and miR-200c found that TGF␤R1 was a target for these miRNAs with six seed matches in the rat.…”
Section: Discussioncontrasting
confidence: 53%
“…While TGF-β lowers E-cadherin, CTGF (a driver of partial EMT) increases E-cadherin expression. In the nondiabetic context, an increase in E-cadherin has been recently reported in rats with ureteral obstruction, a classical model of EMT-mediated kidney fibrosis (144). Further studies are needed to better understand the relevance, the molecular signature, and the therapeutic potential of EMT in the diabetic kidney, especially in human.…”
Section: The Unique Growth Phenotype and Morphological Changes Of Thementioning
confidence: 99%